Microarchitected compliant scaffolds of pyrolytic carbon for 3D muscle cell growth - Taale, Mohammadreza; Schamberger, Barbara; Monclus, Miguel A.; Dolle, Christian; Taheri, Fereydoon; Mager, Dario; Eggeler, Yolita M.; Korvink, Jan G.; Molina-Aldareguia, Jon M.; Selhuber-Unkel, Christine; Lantada, Andrés Díaz; Islam, Monsur (Advanced healthcare materials, 2023)
The integration of additive manufacturing technologies with the pyrolysis of polymeric precursors enables the design-controlled fabrication of architected 3D pyrolytic carbon (PyC) structures with complex architectural details. Despite great promise, their use in cellular interaction remains unexplored. This study pioneers the utilization of microarchitected 3D PyC structures as biocompatible scaffolds for the colonization of muscle cells in a 3D environment. PyC scaffolds are fabricated using micro-stereolithography, followed by pyrolysis. Furthermore, an innovative design strategy using revolute joints is employed to obtain novel, compliant structures of architected PyC. The pyrolysis process results in a pyrolysis temperature- and design-geometry-dependent shrinkage of up to 73%, enabling the geometrical features of microarchitected compatible with skeletal muscle cells. The stiffness of architected PyC varies with the pyrolysis temperature, with the highest value of 29.57 ± 0.78 GPa for 900 °C. The PyC scaffolds exhibit excellent biocompatibility and yield 3D cell colonization while culturing skeletal muscle C2C12 cells. They further induce good actin fiber alignment along the compliant PyC construction. However, no conclusive myogenic differentiation is observed here. Nevertheless, these results are highly promising for architected PyC scaffolds as multifunctional tissue implants and encourage more investigations in employing compliant architected PyC structures for high-performance tissue engineering applications.